In vitro and in vivo biological approach to validate folkloric claims of Trianthema triquetra Rottler & Willd (Bangladesh Journal of Botany, 2021)
Trianthema triquetra Rottler & Willd (Tt.Cr) is used in traditional practices as a remedy for various ailments. Hence current research was commenced to authenticate the folkloric uses. To discover spasmolytic potential, Tt.Cr was applied to isolate jejunum, while isolated tracheal and aorta tissues were used to determine the tissue relaxing properties of the extract. Anti-lipoxygenase activity was determined in vitro using Baicalein as standard. In vivo testing was carried to examine the potentiality of the herb to treat pyrexia and pain. Tt.Cr showed dose-dependent (0.01 - 3.0 mg/ml) spasmolytic effects in jejunum tissues and relaxed K+ (80 mM)-induced spasm and triggered rightwards shift of Ca+2 concentration-response curves. Carbachol (1μM)- together with K+ (80 mM) - induced tracheal spasm was also relaxed by Tt.Cr (0.01 to 1.0 mg/ml). Additionally, Tt.Cr (0.01 - 1.0 mg/ml) relaxed phenylephrine (1 μM) and K+ (80 mM) - treated constricted rabbit aorta. Tt.Cr (0.5 mM) inhibited lipoxygenase enzyme. Tt.Cr (80 mg/kg) settled pyrexia in rabbits comparable to aspirin and prolonged tail deflection time in mice (100 mg/kg) hence proving analgesic activity. The Tt.Cr demonstrated antispasmodic, bronchodilation and vasodilation properties probably by blocking calcium channels. These outcomes generate logic behind ancient application of herb for numerous ailments such as asthma, cough, heart problems and spasm.